On radially symmetric solutions of the Neumann boundary value problem for the p-Laplace equation - A. S. Tersenov; R. C. Safarov (Учёные записки Казанского университета: Серия Физико-математические науки, 2025)
The Neumann boundary value problem for the p-Laplace equation with a low order term that does not satisfy the Bernstein–Nagumo condition was studied. The solvability of the problem in the class of radially symmetric solutions was investigated. A class of gradient nonlinearities was defined, for which the existence of a weak Sobolev radially symmetric solution that has a H¨older continuous derivative with exponent 1 p−1 was proved.